How nutrition knowledge of coaches, athletic trainers, and strength and conditioning specialists translates to their athletes - Carbone, A. (East Tennessee State University, 2021)
The basis of dietary habits is linked to an individuals` nutrition knowledge; for collegiate athletes this is the difference between optimal performance and falling short. To understand how nutrition information is disseminated to student-athletes, this research surveyed the athletes themselves and their sports staff (coaches, athletic trainers, and strength and conditioning specialists) on their current knowledge. Sport staff and student-athletes at East Tennessee State University were given the opportunity to participate in a 52-question online survey that tested both their general and sports-related nutrition knowledge. While the study sample size did not allow for statistical analyses required to address all three research questions, findings did indicate some variation between teams on measures of nutrition knowledge, and there was a statistically significant difference between sport staff and athletes` general and sport nutrition knowledge. This study aimed to understand if nutrition knowledge of sport staff directly affects that of their corresponding athletes.